16 Myocardial extracellular volume in patients with aortic stenosis undergoing valve intervention: a multicentre T1 mapping study. (March 2019) - J Everett, Russell; A Treibel, Thomas; Fukui, Miho; Lee, Heesun; Rigolli, Marzia; Singh, Anvesha; Bijsterveld, Petra; Tastet, Lionel; Al Musa, Tarique; Dobson, Laura; Chin, Calvin; Captur, Gabriella; et al.
Abstract : Background: Diffuse myocardial fibrosis is a key decompensation mechanism in advanced aortic stenosis (AS) and can be quantified using CMR T1 mapping techniques. Purpose: To assess T1 mapping measures of fibrosis in patients with severe AS referred for aortic valve replacement, and determine their associations with clinical characteristics, disease severity and clinical outcome. Methods: In this international prospective cohort study, patients with severe AS underwent CMR at 1.5T and 3T (Siemens/Philips) with T1 mapping prior to AVR. Image analysis was performed (CVI42, Circle) by a single core laboratory for three T1 mapping measures (native T1, extracellular volume fraction [ECV%] and indexed extracellular volume [iECV=LVMi*ECV%]). Results: Four-hundred patients (70±10 years, 60% male) from nine international centres (Canada/Germany/Korea/USA/UK) were enrolled (including 144 patients from BSCMR AS700 study). AVR was performed (SAVR: n=342, TAVI: n=58) 19 [4-61] days following CMR, with median of 3.8 [1.7–4.5] years follow-up and 40 deaths recorded. As expected, native T1 was higher at 3T than 1.5T (1213±57 versus 1050±48 ms, p<0.001); ECV% did not vary by scanner manufacturer, field strength or T1 mapping sequence (all p>0.30); therefore, only ECV-based measures were analysed. ECV% correlated with increasing age, Society of Thoracic Surgeons Predicted Risk of Mortality score, known coronary artery disease, lower aortic valve peak velocity, increased LV mass, presence of late gadolinium enhancement (LGE) and reduced LVEF (p<0.05 for all). Following adjustment for demographic and clinical variables, ECV% remained associated with both LVEF (p<0.001) and mass index (p=0.043). Similar associations were seen with iECV. A progressive increase in all-cause mortality was seen across tertiles of ECV% (14.0, 28.5 and 53.7 deaths per 1000 patient-years; log-rank test, p=0.003). ECV% was independently associated with all-cause mortality following adjustment for age, sex, peak velocity, impaired LVEF and presence of LGE (HR per% increase in ECV%: 1.13, 95%, 1.04–1.24, p=0.006). iECV was associated with all-cause mortality following adjustment for age and sex (HR 1.03 95% 1.00–1.06, p=0.04) but not after adjustment for the above clinical variables. Conclusion: In patients with severe AS scheduled for AVR, extracellular volume-based T1 mapping measures are robust, track with LV decompensation, and independently predict late all-cause mortality.